LANGUAGE STYLE USED BY MARIO TEGUH IN HIS MOTIVATIONAL PICTURES ABOUT LOVE - HAJAM, HAFIF HELMI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Language style based on diction, language style based on sentence structure, motivational picture The effective communication between one and other people will be running well if they use language variation in different situation. Language variation or language style is the way of someone in using his language in particular occasions by showing his/her personality and character. In conducting the study, the researcher formulated two problems of study namely: (1) What kinds of language style are used by Mario Teguh in his motivational picture about love seen from its diction, and (2) What kinds of language style are used by Mario Teguh in his motivational picture about love seen from its sentence structure. Based on those problems, the researcher formulates the objectives of this study as follows: (1) to find out the kinds of language style used by Mario Teguh in his motivational picture about love seen from its diction, and (2) to find out the kinds of language style used by Mario Teguh in his motivational picture about love seen from its sentence structure.    This study used qualitative analysis since the data of this study were texts in the motivational picture of Mario Teguh. In conducting this study, the researcher used some tables to categorize the data into language style based on diction and language style based on sentence structure. The main theory used in this study is the language style theory proposed by Keraf (2010), Wales (2001), and Chaer (2006). From 20 motivational pictures analyzed based on diction, the researcher found out that there were eleven texts categorized into formal language style, seven texts categorized into informal language style and two texts categorized into the combination of formal and informal language style. Based on sentence structure, it was found that nine texts were categorized into climax style, four texts categorized into anticlimax style, two texts categorized into parallelism, three texts categorized into antithesis style and five texts categorized into repetition style.Finally, the researcher suggests that the further study about language style be conducted in different ways according to the problems of study, object of the study and theory used in the study. The researcher also suggests the next researchersconduct the study which focuses on language style in the spoken form especiallylanguage style based on meaning and tone.